Gugat Cerai dalam Pernikahan Sirri di Pengadilan Agama Kajen (Studi Putusan Nomor 539/Pdt.G/2020/PA.Kjn) - Burhanudin, Slamet (Al-Hukkam: Journal of Islamic Family Law, 2022)
The case of divorce lawsuits in unregistered marriages filed at the Kajen Religious Court can be accepted and decided in Decision Number 539/Pdt.G/2020/PA.Kjn, with the verdict of the Judge requesting the Plaintiff's divorce suit for unregistered marriages and imposing bai'in divorce sughro. The problem in this study is how the judge's consideration in filing a lawsuit in marriage and the decision against the Plaintiff and Defendant. This research is a normative legal research (juridical normative) conducted at the Kajen Religious Court using a law approach, a conceptual approach, and a case approach. The results of this study the authors found that the consideration in the plaintiff's divorce application, the judge first declared the marriage valid and then divorced the plaintiff and the defendant after being convinced that there was a crime if it had been submitted, according to the author, the judge's consideration was in accordance with Islamic law and applicable legal rules. And the award can be seen from the position of the Marriage Certificate as legal evidence.